Implicit memory and transformative learning theory: Unconscious cognition. - Edward W. Taylor (Adult Education Research Conference, 1997)
Recent research has found that the transformation of meaning structures (schemes and perspectives) can occur without critical reflection. This phenomenon seems to be explained by a concept called implicit memory – the unconscious development of thoughts and actions. This paper involves a review of related literature on implicit memory from the fields of neurobiology and psychology and its implications for the theory and practice of transformative learning